PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN TERHADAP MOTIVASI BELAJAR MAHASISWA IKIP SILIWANGI BANDUNG - Pipit Puspitasari; Puspita Sari Jaya Putri; Woro Wuryani (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This study aims to know the effect of the use of learning media on the motivation of students learning IKIP Siliwangi. The research method used is descriptive qualitative, the sample of this study is a student of IKIP Siliwangi covered from several faculties and majors, including faculty of language with Indonesian and English majors, science faculty with majoring in mathematics education, faculty of science majoring in primary school teacher education, counseling guidance, paud teacher education, and out-of-school education. By limiting 30 students of IKIP Siliwangi, the instrument used is a questionnaire created through from google. The results method of this study indicates that there is a significant influence due to the fluse of learning media on the students motivation of IKIP Siliwangi.